LANGUAGE BARRIERS IN LEARNING ENGLISH FOR YOUTH ALBANIAN IMMIGRANTS IN ENGLAND - Greta Jani; Doliana Celaj (Езиков свят)
The emigration of Albanians to England has increased significantly in recent years, making the role of using and learning the English language decisive, especially for the Albanian youths who attend school. The purpose of studying the English language encompasses various aspects such as education, economics, social integration, and more. This study explores the language barriers young immigrant Albanians face in England when learning English, as well as the unique factors that influence their experiences in school. The study involved the observation of 75 Albanian youths, 30 males and 45 females. The problems caused by mastering the mother tongue are related to grammar, vocabulary, and articulation. Given the connections between culture, language, and individuality, cultural concerns emphasise how crucial it is to include different cultures in the classroom. The study suggests educational approaches, such as bilingual classes, to address language barriers and promote fluency in Albanian and English. Adding Albanian social aspects to culturally sensitive curriculum and teaching is recommended to improve student interaction and foster a sense of belonging. The study recommends teacher preparation courses that emphasise barriers to linguistic and cultural sensitivity, to improve the capacity of teachers to deal with particular issues. The research suggests a comprehensive, collaborative strategy that combines educators, communities, and legislators to create a welcoming and encouraging atmosphere for successful language learning in English through the skills and social inclusion of Albanian youth immigrants.